Diuretics and risk of lower extremity amputation amongst patients with insulin-treated type 2 diabetes – exploring the mechanism of possible sodium glucose co-transporter 2 inhibitor induced risk of lower extremity amputations. (1st December 2020) - Alshnbari, Afnan; Alkharaiji, Mohammed; Anyanwagu, Uchenna; Idris, Iskandar
Abstract: Aims and background: Sodium-glucose cotransporter-2 (SGLT2) inhibitor has been linked to an increased risk of lower extremity amputation (LEA) in patients with Type 2 Diabetes (T2D) and is known to induce volume depletion through osmotic diuresis. We investigated the potential association between diuretics use and the LEA risk in insulin-treated T2D patients. Methods and materials: A retrospective cohort study was conducted on 10, 320 insulin-treated T2D patients within the UK population. Cox proportional hazard models were utilised to estimate LEA hazard ratios. Amputation risk was compared between a propensity score-matched cohort of diuretics users versus non-users over a 20-year period. Results: Among 10, 320 subjects, 6454 (52.3%) were on diuretics. In the full cohort, diuretic-treated patients had significantly higher risk of LEA than the non-diuretic individuals (HR: 1.89; 95%CI: 1.34–2.68). When adjusting for possible confounding effects, a 2.3-fold higher risk of amputation was observed (aHR: 2.45; 95%CI: 1.63–3.69). In the matched cohort ( n = 580), this association is marginally significant (HR: 3.33; 95%CI: 1.17–18.9; p = .029). Conclusion: While diuretic use appeared to be associated with an increased risk of LEA among insulin-treated T2D patients, this association is marginally significant after controlling for confounding factors by cohort matching. These results suggest that volume depletion may be a factor in increasing the risk of LEA amongst high-risk T2D patients, but the strength of this association is weak when adjusted for all other risk factors. Thus, patient selection is crucial when determining the safe use of agents that induce volume depletion in high risk patients with T2D.